2020
DOI: 10.1364/josab.379261
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement dynamics of moving qubits in a common environment

Abstract: In this paper we provide an analytical investigation of the entanglement dynamics of moving qubits dissipating into a common and (in general) non-Markovian environment for both weak and strong coupling regimes. We first consider the case of two moving qubits in a common environment and then generalize it to an arbitrary number of moving qubits. We show that for an initially entangled state, the environment washes out the initial entanglement after a finite interval of time. We also show that the movement of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 65 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…Based on the Hamiltonian about the moving-qubit in [52] and the Hamiltonian about the classical driving in [53], we construct a moving-biparticle model driven by classical field, in which the moving-biparticle system couples with a length of L (L approaches infinity), and the particles move along the z-axis and are driven by an external classical-field (see figure 1). Meanwhile, in order to effectively control the quantum effect of qubits, the classical field is polarized along the x-axis and propagates along the y-axis.…”
Section: Physical Model and Analytical Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the Hamiltonian about the moving-qubit in [52] and the Hamiltonian about the classical driving in [53], we construct a moving-biparticle model driven by classical field, in which the moving-biparticle system couples with a length of L (L approaches infinity), and the particles move along the z-axis and are driven by an external classical-field (see figure 1). Meanwhile, in order to effectively control the quantum effect of qubits, the classical field is polarized along the x-axis and propagates along the y-axis.…”
Section: Physical Model and Analytical Solutionmentioning
confidence: 99%
“…In particular, the authors at [52] first investigated the dynamics of entanglement of two moving qubits in a common environment for both strong and weak coupling regimes, and then generalized to the case that an arbitrary number of qubits interact with an environment. They obtained the stationary state of each case in details and also illustrated that how the motion of qubits affects the dynamics of entanglement.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Y. J. Zhang and W. Han studied the evolution process of an open stationary system driven by external classical field and found that the classical field can effectively speed up the evolution of the stationary qubit [51]. A. Mortezapour and D. Park et al studied the entanglement and coherence of an open moving-qubit by assuming the length of the cavity is close to infinity, and their results showed that the entanglement and coherence can be protected from decay by suitable adjusting the velocity of the qubit [52][53][54][55].The authors in [56] investigated recently the entanglement dynamics of an open moving-biparticle system driven by classical-field and the results showed that the classical driving can not only protect the entanglement, but also effectively eliminate the influence of the qubit velocity and the detuning on the quantum entanglement. Inspired by these works, we construct a model of an open moving-qubit driven by external classical field in order to understand the influence of the classical field and the velocity of moving-qubit in an infinite zero-temperature cavity on quantum evolution process.…”
Section: Introductionmentioning
confidence: 99%
“…[60,61] In a very recent paper, the authors showed the positive role of movement of qubits on the entanglement dynamics of an arbitrary number of qubits in a Markovian and/or non-Markovian environment. [62] It has also been shown that when all of the qubits have the same velocity, the stationary state of entanglement is independent of the velocity of qubits. [62] All of the statements mentioned above motivate us to examine the effect of movement of qubits on the entanglement swapping between two separate subsystems.…”
Section: Introductionmentioning
confidence: 99%
“…[62] It has also been shown that when all of the qubits have the same velocity, the stationary state of entanglement is independent of the velocity of qubits. [62] All of the statements mentioned above motivate us to examine the effect of movement of qubits on the entanglement swapping between two separate subsystems. To end this, we consider two independent cavities, each contains a moving two-level system (qubit) in the presence of dissipation.…”
Section: Introductionmentioning
confidence: 99%